Correlational study of interleukin-6 with albuminuria in type 2 diabetes mellitus - Vaishya, Ganga Prasad; Kumar, Granth; V., Vijayavarman; Pandey, Sanjeev Kumar; Kumar, Arun; K., Kiran (International Journal of Research in Medical Sciences, 2019)
Background: Individuals with type 2 diabetes display features of low-grade inﬂammation. Mediators of inﬂammation such as IL-6 have been proposed to be involved in the events causing as well as progression of diabetes. Diabetic nephropathy is one of the commonest causes of chronic kidney failure throughout the world. Although diabetic nephropathy is traditionally considered a non-immune disease, accumulating evidence now indicates that immunologic and inflammatory mechanisms play a significant role in its development and progression. Methods: This cross sectional study was conducted in the department of medicine, UPUMS, Saifai. The study was conducted from June 2018 to February 2019. A total of 80 type 2 diabetes patients were included in the study. After informed consent, patients were recruited. FBS, PPBS, HbA1C, 24 Hrs Urinary protein and interleukin-6 levels were measured. The data was analysed using SPSS 23. Pearson co relation co efficient was determined between IL -6, HbA1c and Urinary protein. Result: A total of 80 type 2 diabetes patients were studied. The study subjects were divided into 3 groups based on the urinary protein level into normo-albuminuria, Micro- albuminuria and macro- albuminuria. FBS, PPBS, HBA1c, 24 Hrs Urinary protein and Interleukin – 6 were significantly associated with proteinuria (p<0.001). Urinary protein was positively correlated with IL-6 (R2=0.57, p<0.01). The blood glucose was positively correlated with IL-6 (R2=0.413, p-0.01). Conclusion: Raised IL-6 levels in diabetics revealed the presence of inflammation. Our study showed positive correlation between IL-6, HBA1c and Urinary protein.